Description Of Error Use Of Indonesian Speaking In Stories Completed Of Elementary School Students - Ady Saputra (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The purpose of this study was to describe the Indonesian spelling errors of sixth grade students at SDN 029 Tarakan in writing essays. This becomes a reflection material for teachers, students and schools to make improvements and pay more attention to students' writing skills. Teachers must know the errors in using EBI (Indonesian Spelling) contained in the stories written by students so that mistakes do not occur in other learning. This research also helps students in improving their writing skills. This study uses a qualitative method, namely document review. The results of this study obtained 1) Errors in the use of letters in student essays amounted to 33% of error cases. 2) Word writing errors in students' stories are 27% of error cases. 3) Errors in using punctuation in students' stories are 40% of error cases. The results of this study are expected that teachers who teach focus on providing knowledge, practice and application of the writing process approach, especially Indonesian spelling in essays. And the teacher is able to strive and foster student interest in writing so that students' works are also increasing.